2006
DOI: 10.4049/jimmunol.176.8.4530
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Insufficient Perforin Expression in CD8+ T Cells in Response to Hemagglutinin from Avian Influenza (H5N1) Virus

Abstract: Hypercytokinemia has been considered to be responsible for hemophagocytosis and multiorgan failure in severe human cases of H5N1 viral infection. In this study, we show a recombinant hemagglutinin (H5) from a H5N1 virus may suppress the perforin expression and reduce cytotoxicity of human CD8+ T cells to kill H5-bearing cells. The persistence of H5-presenting cells provides sustained stimulation and leads to a marked lymphoproliferation and IFN-γ hyperproduction. We propose the IFN-γ hyperproduction may explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 14 publications
0
54
0
Order By: Relevance
“…They occur in the context of severe viral infections, especially Epstein-Barr virus infection, cancer, and autoinflammatory and autoimmune diseases, in all age groups. 3,21,22 The probably diverse mechanisms that lead to secondary HLH are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…They occur in the context of severe viral infections, especially Epstein-Barr virus infection, cancer, and autoinflammatory and autoimmune diseases, in all age groups. 3,21,22 The probably diverse mechanisms that lead to secondary HLH are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of lymphopenia induced after H5N1 influenza virus infection is largely unknown. Remarkably, H5N1 influenza virus seems to reduce the effector function of CD8 + T cells by an insufficient perforin expression (10). Moreover, it was reported that H5N1 viruses are able to infect cells of the immune system, leading to an impaired adaptive immune response (11).…”
Section: Nfluenza a Virus Infection Causes Severe Disease In Humansmentioning
confidence: 99%
“…This so-called cytokine storm could pathogenically contribute to tissue damage and progressive systemic organ failure. Improper intracellular trafficking and impaired apoptosis have also been implicated [1,20,21]. The strikingly inflammatory state promoted by hypercytokinemia could explain the beneficial role of high dose steroids that we observed.…”
Section: Comorbidities/ Co-morbid Infectionsmentioning
confidence: 52%
“…Unfortunately, treatment was never started in many cases because of delayed diagnosis. In the study by Beutel et al [14], the median time from the onset of symptoms to the diagnosis of VAHS was 23 days (interquartile range [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. This could explain, at least in part, the poor prognosis of HPS secondary to influenza A infection.…”
Section: Comorbidities/ Co-morbid Infectionsmentioning
confidence: 99%
See 1 more Smart Citation